ОСОБЛИВОСТІ ВИЯВЛЕННЯ, РОЗСЛІДУВАННЯ КОНТРАБАНДИ НАРКОТИЧНИХ ЗАСОБІВ, ЩО ВЧИНЯЄТЬСЯ ОРГАНІЗОВАНИМИ ЗЛОЧИННИМИ ГРУПАМИ - Рудницький, Іван Львович (SUPREMANCE OF LAW, 2019)
The article attempts to investigate the specifics of detection through investigative (investigative) ««public» and covert actions, investigating the smuggling of narcotic drugs, psychotropic substances, their analogues or precursors, which is committed by organized criminal groups. Defined weekend procedural, operational search and other platforms for the investigation of this crime.